Ascaris lumbricoides egg die-off in an experimental excreta storage system and public health implication in Vietnam - Tu Vu-Van; Phuc Pham Duc; Winkler, Mirko S.; Zurbrugg, C.; Zinsstag, Jakob; Huong Le Thi Thanh; Tran Huu Bich; Hung Nguyen-Viet (Springer, 2017)
Objectives We studied the influence of different additive materials (lime, and rice husk) and aeration conditions on Ascaris lumbricoides egg die-off in 24 vaults of an experimental excreta storage unit. Methods Excreta samples were collected once every two weeks over a 181-day period. Temperature, pH, and moisture content were recorded. A. lumbricoides eggs were quantitatively analyzed by the Romanenko method, which identified and counted live and dead eggs. Results From the first sampling (0 storage day) to the final sampling (181 storage days) the average percentage of viable A. lumbricoides eggs decreased gradually from 76.72 ± 11.23% (mean ± SD) to 8.26 ± 5.20%. The storage time and the high pH value significantly increased the die-off of helminth eggs. Over 181 storage days, all vaults option effectively reduced A. lumbricoides eggs die-off. Conclusions The best vault option, with aeration and 10% lime per total weight, met the WHO standard for excreta treatment on the 111th storage day.